Detection of convective systems through surface wind gust estimation based on Sentinel‐1 images: A new approach. (18th October 2018) - La, Tran Vu; Messager, Christophe; Honnorat, Marc; Channelliere, Claire
Abstract : Convective system (CS) tracking and identification are mainly based on the analyses of brightness temperature and precipitation. Few studies reported about the detection of CSs through surface wind gust estimation due to CS downdraft reaching sea surface. Based on high‐resolution Sentinel‐1 images, this study proposes the detection of CS signatures through an enhancement of surface wind magnitude in the vicinity of CSs. The CMOD5.N and Sapp's model (CMOD‐like function) are used for the retrieval of surface wind speed from VV‐pol and HH‐pol images, respectively. Based on numerous cases, the study presents the retrieved winds from two representative Sentinel‐1 images acquired over the Gulf of Mexico, on which several types of CS effect on sea surface (i.e., round form, convection line) are detected. Wind gust produced by the downdraft associated to these CSs exceeds 20–25 m/s. In order to verify whether the detected wind gust is associated to CSs, moderate/heavy precipitation extracted from the Next‐Generation Radar (NEXRAD) images is used as an additional assessment. Abstract : Sketch of wind speed estimation from Sentinel‐1 images based on CMOD5.N (Hersbach, 2008) and the Sapp's model (Sapp et al ., 2016) for VV‐pol and HH‐pol data, respectively.